2023
DOI: 10.1002/jso.27279
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive factors in undifferentiated pleomorphic sarcoma: A long‐term study from a large tertiary care urban center

Abstract: Background and Objectives Undifferentiated pleomorphic sarcoma (UPS) is an aggressive type of soft tissue sarcoma (STS) with high rates of metastatic disease and local recurrence. We sought to identify risk factors for local recurrence, metastasis, and overall death, and assess their impact on overall survival (OS), local recurrence‐free survival (LRFS), and metastasis‐free survival (MFS). Methods A total of 386 cases of UPS treated at our institution from 1980 to 2020 were included. Cox proportional hazards r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In this regard, a recent study on appendicular undifferentiated pleomorphic sarcoma reported that a 7-cm cutoff value provided superior prognostic value compared to standard STS T-score thresholds. 13 Surgical management of these tumors is challenging because of their invasive nature and the complex anatomy of the foot and ankle region. Unlike other anatomic areas, this region lacks clear anatomical barriers between compartments and has a small soft tissue envelope, making limb salvage surgery difficult and often resulting in the need for amputation when achieving negative margins is unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, a recent study on appendicular undifferentiated pleomorphic sarcoma reported that a 7-cm cutoff value provided superior prognostic value compared to standard STS T-score thresholds. 13 Surgical management of these tumors is challenging because of their invasive nature and the complex anatomy of the foot and ankle region. Unlike other anatomic areas, this region lacks clear anatomical barriers between compartments and has a small soft tissue envelope, making limb salvage surgery difficult and often resulting in the need for amputation when achieving negative margins is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent study on appendicular undifferentiated pleomorphic sarcoma reported that a 7-cm cutoff value provided superior prognostic value compared to standard STS T-score thresholds. 13…”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive study on UPS, an analysis of 386 cases identified lymph node involvement, age over 60, and tumors larger than 7 cm as significant risk factors for local recurrence and distant metastasis. 40 Another study that investigated overall survival in patients with STS of the extremity and thoracic wall noted that a deep tumor location and a grade higher than 2 were correlated with an increased rate of local recurrence. 32 Additionally, Houdek et al described the commonality of local recurrence and distant disease following wide excision of STS in the foot and ankle, including worse OS in tumors ≥3 cm.…”
Section: Prognostic and Predictive Factors For Stsmentioning
confidence: 99%
“…Chest imaging has often been considered adequate for UPS; however, one study showed that approximately 1/3rd of the cohort of patients with UPS demonstrated bony metastasis in the observation period, and over 40% of those that had metastatic disease on presentation were found to have bony metastasis. 40 These unexpected findings bring to question whether patients with UPS might be better staged/surveilled with bone scintigraphy or PET CT. The authors also highlight the prognostic value of lymphovascular infiltration and postulate that PET CT might be the preferred imaging modality for staging and surveillance in this population.…”
Section: Staging and Surveillancementioning
confidence: 99%
“…The generally accepted treatment involves radical surgical resection followed by chemotherapy or radiotherapy, depending on the tumour size or the presence of metastatic disease. Despite such aggressive therapy, recurrence rates range after 5 years range between 10 and 42%, whilst 31 to 40% develop distant metastasis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%